Blended learning atau full online: Meningkatkan mood dan motivasi siswa selama era new normal - Aru Fantiro, Frendy; Arifin, Bustanol; Muzakki, Abdurrohman; Setiawan, Edi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
The purpose of this study is to improve students' mood state and motivation to learn through blended learning versus full online. This research is quantitative with the use of experimental methods. Participants in this study were students from University of Muhammadiyah Malang (n=42) who take physical education courses. The forty-two participants were allocated to the blended learning group (n=21) and full online group (n=21). The instruments in this study used the mood states and motivation questionnaire. The intervention program was carried out for four weeks with three weekly meetings. The raw data in this study will be analyzed using the SPSS application to find the mean and standard deviation, normality test, and homogeneity test. Independent sample t-test was used to test the difference in pre-test and post-test mood state scores and student motivation. The level of significance used in this study is 0.05. The study results found that there was a significant difference in effect between blended learning and full online and the data proved that blended learning had a better effect than full online. This research contributes to developing a learning system that can be used in the new normal era so that lecturers can create optimal lectures.